Effect of BMI on the clinical and radiological outcomes of pilon fractures - ELMALI, NURZAT; CECEN, Gultekin Sitki; GULABI, Deniz; YANIK, Erman; PEHLIVANOGLU, Gokhan; BEKLER, Halil; Elmali, NURZAT (My University, 2014)
Objective: The aim of this study was to evaluate the effect of BMI on clinical and radiological outcomes of pilon fractures. We hypothesized that obese patients, defined as having a BMI of 30 or higher, would not have worse functional and radiological outcome compared to non-obese patients.